Pengembangan Suplemen Bahan Ajar Geografi Pariwisata pada Materi Potensi Ekowisata di Kawasan Teluk Tomini - M. Iqbal Liayong Pratama; Sri Maryati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
The implementation of research and development aims to develop supplementary teaching materials for tourism geography courses. The supplemental teaching materials produced are printed teaching materials that contain contextual content about the potential of ecotourism in the Tomini Bay Area. The research was conducted using research and development methods. The process of collecting data was done using observation, interviews and questionnaires. The development of teaching materials uses a 4D development model, which includes four stages, namely define, design, development, and disseminate. The final result of the teaching material supplement validation was 4.32, the linguist gave a final score of 4.28, and the tourism expert gave the final score of 4.25. The validation results of the teaching material supplement indicate that the teaching material supplement is in the very feasible criteria and can be used in the process of lecturing activities.